Distinguishing the lipid profile of GCK-MODY patients and its correlation with hsCRP levels - Ping, Fan; Fu, Junling; Xiao, Xinhua (Frontiers in Endocrinology, 2022)
Aims:Glucokinase (GCK)-MODY is the most common monogenic diabetes in China. We have previously reported on the low levels of high-sensitivity C-reactive protein (hsCRP) in patients with GCK-MODY. In this study, we further explored the correlation between serum lipid profiles and hsCRP levels among patients with different types of diabetes, also proposed to find out the possible mechanism of macrovascular protection in GCK genetic variants.Methods:Serum lipid profiles of GCK-MODY group (n=50) were compared with that of hepatocyte nuclear factor 1-alpha (HNF1A)-MODY group (n=19), T1DM (n=50) and T2DM (n=54). The associations between the lipid compositions and high-sensitivity C-reactive protein (hsCRP) levels in each group were also explored.Results Elevated high-density lipoprotein-cholesterol (HDL-C) levels were found in GCK-MODY group (1.5±0.27) compared with the groups of T1D (1.2±0.47, P<0.01) and T2D (1.3±0.3, P<0.01). Meanwhile, a significantly lower LDL-C level (2.4±0.69) in GCK-MODY group compared with T1DM(2.7±0.72, P<0.01) and T2D(2.9±0.68, P<0.01) was also noted. A lower ratio of Triglyceride to HDL-C (TG/HDL) as well as a lower hsCRP level were also found in GCK-MODY group (TG/HDL ratio 0.38 (0.25-0.52), hsCRP 0.2mg/L (0.16-0.37)) compared with those in T1D (TG/HDL ratio 0.56 (0.39-1.29), hsCRP 0.56mg/L (0.39-1.29), P<0.01) and T2D ((TG/HDL ratio 1.6 (1.1-2.68), hsCRP 1.11mg/L (0.66-2.34), P<0.01). Although HNF1A-MODY subjects had similar hsCRP levels (0.17(0.08-0.52)) compared with GCK-MODY group, they had the higher TG levels(1.01(0.66-1.76), P<0.05) as well as TG/HDL ratios(0.84(0.56-1.31), P<0.05). Analysis of correlations between hsCRP and lipid profiles in each group confirmed that the LnhsCRP (natural logarithm transformed hs-CRP level) was positively correlated with LnTG (r= 0.352, P=0.011) as well as LnTG/HDL ratio (r=0.283, P=0.047) only in individuals with GCK-MODY. Conclusions:Individuals harboring GCK variants have characteristics of protective lipid profiles manifest in a higher level of HDL-C as well as a lower LDL-C level compared with T1DM and T2DM subjects. In addition, the lower ratio of TG/HDL level were found associated with inhibition secretion of hsCRP even if adjusted for HbA1c levels in subjects with GCK-MODY. It is suggested that the protective effect of macrovascular complication in the GCK-MODY patients might partly be due to their unique lipid profiles associated with suppression of inflammation.